(untitled) (Bangladesh Agronomy Journal, 2025)
Poor-quality potatoes are the key constraint on growth and development of Bangladesh’s potato processing industry. This study aims to investigate the potential benefits of using vermicompost and biochar in conjunction with recommended dose of fertilizers (RDF) to improve potato yield and quality. The research study was performed at the research field of Sher-e-Bangla Agricultural University (SAU) in Dhaka, Bangladesh, from November 2023 to April 2024. The study utilized a split-plot design with three replications to assess the impacts of four different levels of biochar (B) and vermicompost (Vm): B1 (0 t ha−1), B2 (1.5t ha−1), B3 (3.0 t ha−1), and B4 (4.5 t ha−1), and Vm1 (0 t ha−1), Vm2 (1.5 t ha−1), Vm3 (3.0 t ha−1), and Vm4 (4.5 t ha−1) on yield and quality of potato. The results demonstrated significant effects of biochar and vermicompost on a wide range of yield and quality parameters studied in this experiment. All of these trends were generally positive, with an increase in the amount of applied biochar and/or vermicompost, except for a decrease in reducing sugar content, which is harmful constituent of potato. Among the treatment combinations, B4Vm4 produced the highest tuber yield at 32.47 t ha−1 with its corresponding marketable yield at 32.07 t ha−1 and yield of potato suitable for French fry production at 6.37 t ha−1. It is statistically comparable to the B4Vm3, B3Vm4, and B3Vm3. The quality in terms of specific gravity and starch content was higher in B4Vm4 with 1.068 g cm−3 and 18.45 mg g−2 fresh weight, respectively. However, B4Vm3, B3Vm4, and B3Vm3 are statistically comparable. So, potato farmers can use 3 tons per hectare of biochar and vermicompost, in addition to RDF, which includes 325-220-250-120-14 kg ha−1 of urea, TSP, MoP, Gypsum, and zinc sulfate for producing good quality potato without sacrificing yield. Bangladesh Agron. J. 2025, 28(1): 46-56